OPTIMIZATION OF THE "PROSECUTOR IN SCHOOL" PROGRAM THROUGH SOCIAL MEDIA IN CIREBON CITY - Alfiana, Kartika; Firdaus, Firza Aulia; El Adawiyah, Fabiani Nur Ayesha; Azzahra, Lutvia Aulia; Waluyadi, Waluyadi (Jurnal Abdisci, 2025)
Abstract: Background. Low legal awareness among students is a serious challenge in creating a law-abiding generation. The "Prosecutor Entering School" program is present as an educational effort, but its implementation is still limited to only a few schools and has not yet reached a wider audience. Given the high use of social media among students, optimizing this program through digital platforms is an important strategy to expand the reach and effectiveness of legal counseling, especially in Cirebon City. Aim. This study aims to analyze the effectiveness of the "School Entrance Prosecutor" Program (JMS) in Cirebon City in increasing legal awareness among students and identifying optimal strategies that can later be applied at the Cirebon City District Attorney's Office. Methods. This study uses a normative juridical method approach. The data used are secondary and primary data. The data collection techniques carried out in this study were literature studies for secondary data and observation through interviews for primary data. Meanwhile, the data was analyzed qualitatively. Results. The results of this study show that digitizing the "School Entrance Prosecutor" Program through social media such as TikTok, YouTube, and Instagram is an effective strategy for delivering legal education in an engaging and easy-to-understand manner for students. Conclusions. This digitalization also expands the reach of legal education to various regions, making it more effective than previous methods. A structured digital strategy and periodic evaluations are needed to ensure the sustainability and effectiveness of the "Prosecutor Enters School" program in the long term.